2019
DOI: 10.1021/acscatal.9b01159
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Trends Between Oxygen Evolution and Chlorine Evolution on Iridium-Based Double Perovskites in Acidic Media

Abstract: The electrochemical chlorine evolution reaction (CER) and oxygen evolution reaction (OER) represent core processes in the production of chlorine, relevant to bulk chemical manufacturing, and water splitting, the most promising technology for renewable energy storage. Unfortunately, because of an apparent coupling between their key binding intermediates, the two reactions can easily occur simultaneously, which is never an attractive outcome. In this work, using a series of iridium-based double perovskites and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
121
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(122 citation statements)
references
References 82 publications
1
121
0
Order By: Relevance
“…33), ClO * species (η TD(CER) = 0.20 V for 2O b 2ClO c ) were found to be closer to the thermoneutral state (ΔG = 0) than Cl * species (η TD(CER) = 0.62 V for 2O b 2Cl c ), implying that ClO * species were identified as the reaction intermediate for the CER on the PtO 2 surface of the PtNP/ CNT, similar to other precious metal oxides, such as RuO 2 and IrO 2 (refs. 14,20,58 ). In summary, we theoretically demonstrated that the CER activity of Pt 1 /CNT was superior to that of PtNP/CNT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…33), ClO * species (η TD(CER) = 0.20 V for 2O b 2ClO c ) were found to be closer to the thermoneutral state (ΔG = 0) than Cl * species (η TD(CER) = 0.62 V for 2O b 2Cl c ), implying that ClO * species were identified as the reaction intermediate for the CER on the PtO 2 surface of the PtNP/ CNT, similar to other precious metal oxides, such as RuO 2 and IrO 2 (refs. 14,20,58 ). In summary, we theoretically demonstrated that the CER activity of Pt 1 /CNT was superior to that of PtNP/CNT.…”
Section: Resultsmentioning
confidence: 99%
“…Mixed metal oxides (MMOs) based on precious metals (Ru and Ir), such as a dimensionally stable anode (DSA), have been predominantly used as CER catalysts irrespective of the pH of the solution [5][6][7][8] . However, computational and experimental works revealed that MMO catalysts are also highly active for the OER, exhibiting a scaling relationship between the CER and OER 13,[17][18][19][20] . This relationship suggests that two reactions are catalysed on a similar active site of the MMOs or form a common surface intermediate species [20][21][22][23][24] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although successful, the coupling of mass-spectrometry with electrochemistry is not without its complications and often has poor temporal resolution. This recently led Koper et al to apply the classical rotating ring disc method of Frumkin, Levich et al 21,22 to enable the local chlorine concentration to be analysed, 23,24 and so to delineate the conditions under which the OER is favourable over the CER on carbon based electrodes. Similarly scanning electrochemical microscopy (SECM) in sample generation-tip collection (SG-TC) or the redox competition (RC) modes can be used for the visualization of the catalytic activity of materials for chlorine evolution.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15,17] Though OER is desired compared to CER for the purpose of this report, we note that certain industries prefer Cl 2 generation for wastewater treatment. [18] Several works have sought to design materials that favor OER by incorporating manganese oxide coatings [19,20] or utilizing non-noble metal-based electrocatalysts. [13,14,17,21,22,23] This competition underscores the complex interplay between CER and OER.…”
mentioning
confidence: 99%